Investigating The Failure of Leaf Springs in Automobile Suspension on Ghana Road - Prince Yaw Andoh Andoh; L D Mensah; D E K Dzebre; Kofi Owura Amoabeng; Charles Kofi Kafui Sekyere (Journal of Applied Engineering and Technological Science (JAETS), 2022)
This study investigates the failure of leaf springs used in the suspension system of heavy-duty vehicles in Ghana. Primary and secondary data were collected using both open and closed-ended questionnaires. Welders and fabricators of Sarkyoyo enterprise at the Suame Spare parts dealership area in Kumasi were engaged in the survey. The elastic strain and stress mathematical models were used to determine the stress points in a loaded leaf spring with the aid of ANSYS. The factors considered in the analysis were the leaf spring SAE design specification, the recommended Ghana Highway Authority load limit for heavy-duty vehicles, and the terrain. Analysis was done for both the standard and variable curvature leaf springs. The mode of failure was found to be fatigue loading. The causes of failure were determined to be loaded beyond the recommended 43 tons per wheel limit, bad roads, and reckless driving. It was also observed that loading causes the edges of the leaf spring to bend outwardly from the top, making the edges more prone to failure. Results further showed that the leaf spring with variable curvature recorded strain energy 2.5 times higher than the standards leaf spring.